Effectiveness in vitro and in vivo of a Camellia sinensis “green tea “ based gel against microorganisms of importance in periodontal processes - Moromi Nakata, Hilda (2011)
Periodontal diseases after dental caries are the most prevalent in the dental health is concerned. The gingivitis and periodontitis are the result of the presence of bacteria and their products capable of altering the tissue and the host response. Studies on action of Camellia sinensis (green tea) on microorganisms of periodontal disease, demonstrates the beneficial effects of this product and the application potential in different areas. Therefore the purpose of the study was to determine the in vivo effectiveness of a gel made from carboximetilcelulosa and alcoholic extract of green tea, and in vitro on microorganisms associated with periodontal disease: P. loeschi, P.anaerobius and Capnocytophaga. The results show the presence of halos of inhibition of green tea extract at concentrations of 100 %, 75 %, 50 % and 25 %, the gel was observed only action on the site of contact, no halo. Regarding the results in patients showed an improvement in gingival index (Loe and Silness) after exposure to gel with green tea extract for up to 2 weeks. We conclude that green tea extract has antibacterial action on ATCC strains of P. loechi, P.anaerobius various concentrations used, but the gel shows only an effect on the site of contact. There was evidence of improvements in the gingival index in patients treated with the gel extract up to 2 weeks of evaluation.